2022
DOI: 10.1029/2022jd037490
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Downscaling the South Asian Summer Monsoon From a Global Reanalysis Using a Regional Coupled Ocean‐Atmosphere Model

Abstract: The South Asian Summer Monsoon (SASM) is one of the most significant sources of terrestrial convection, which exhibits a robust seasonal cycle and is often construed as a significant part of the atmospheric general circulation. The inter-play between the atmosphere and ocean in the evolution of the SASM is complex. It manifests at the interface of ocean-atmosphere and its influence extends well into the free troposphere and much below the ocean surface (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…The CRSM exhibits reasonable skill in simulating the spatial distribution of observed mean summer monsoon mixed layer depth (MLD) features, such as deeper MLD over the western AS and comparatively shallower MLD over the BoB (e.g., Misra et al., 2022). However, CRSM underestimates the magnitude of the MLD in most of the areas and overestimates over certain areas of the northern BoB and certain areas of southern AS (Figure S3 in Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CRSM exhibits reasonable skill in simulating the spatial distribution of observed mean summer monsoon mixed layer depth (MLD) features, such as deeper MLD over the western AS and comparatively shallower MLD over the BoB (e.g., Misra et al., 2022). However, CRSM underestimates the magnitude of the MLD in most of the areas and overestimates over certain areas of the northern BoB and certain areas of southern AS (Figure S3 in Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…The sponge zone's width is set to 16 grid points at the edges of the model boundaries. Earlier studies have indicated that these model physics schemes are the most suitable combination for simulating the ISM (e.g., Misra et al., 2017, 2022).…”
Section: Models Experimental Details and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic downscaling is performed by numerical models to simulate regional physical fields at a finer scale (Giorgi & Mearns, 1999). This method is physically explicit, but requires adequate knowledge of the climatic system as well as substantial computational resources (Misra et al, 2022). By contrast, statistical downscaling is based on statistical models to establish relationships between low‐resolution and high‐resolution variable fields, which are relatively simple and computationally small (Gutiérrez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%